2020
DOI: 10.21203/rs.3.rs-106451/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-145 Inhibits Mitochondrial Function of Ovarian Cancer by Targeting ARL5B

Abstract: Metabolic reprogramming refers to the transformation of the whole metabolic network including glycolysis and mitochondrial metabolism, mainly manifested in Warburg effect and mitochondrial metabolic reprogramming. The roles of miR-145 in glycolysis have been established in ovarian cancer cells. Howerer, its roles in mitochondrial metabolic reprogramming are still unclear. This study aims to identify whether miR-145 regulates mitochondrial metabolic reprogramming in ovarian cancer cells. First, functional exper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…160 Another study showed that an important micro-RNA in the process of tumor development, miR-145, suppresses the Warburg effect and HK2 expression in the human ovarian cancer cell line (SKOV3) and subsequently decreases cancer progression. 162 Berberine promotes Tet Methylcytosine Dioxygenase 3 (TET3)-mediated demethylation of pre-miR-145 to increase inhibition of miR-145 on HK2. TET3 is a protein-coding gene that is located upstream of miR-145 and affects its gene expression.…”
Section: Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…160 Another study showed that an important micro-RNA in the process of tumor development, miR-145, suppresses the Warburg effect and HK2 expression in the human ovarian cancer cell line (SKOV3) and subsequently decreases cancer progression. 162 Berberine promotes Tet Methylcytosine Dioxygenase 3 (TET3)-mediated demethylation of pre-miR-145 to increase inhibition of miR-145 on HK2. TET3 is a protein-coding gene that is located upstream of miR-145 and affects its gene expression.…”
Section: Alkaloidsmentioning
confidence: 99%
“…The reduction in the HIF‐1α expression level decreases the transcription of glucose metabolism‐related genes such as GLUT1 , LDHA , and HK2 160 . Another study showed that an important micro‐RNA in the process of tumor development, miR‐145, suppresses the Warburg effect and HK2 expression in the human ovarian cancer cell line (SKOV3) and subsequently decreases cancer progression 162 . Berberine promotes Tet Methylcytosine Dioxygenase 3 (TET3)‐mediated demethylation of pre‐miR‐145 to increase inhibition of miR‐145 on HK2.…”
Section: Natural Products In Combating Lactate In Cancermentioning
confidence: 99%